PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD BERBASIS PBL (PROBLEM BASED LEARNING) PADA PEMBELAJARAN PENDIDIKAN PANCASILA - Sutrami, Kiki Fitri; Amrullah, Muhlasin (Dharmas Education Journal (DE_Journal), 2023)
The implementation of this research was motivated by the constraints of learning media models that were less imaginative and fun, which made students feel less involved and bored, especially in applying religious characters. The purpose of this research is to create a learning environment with the help of Flash Card media about core values of religious character based on spiritual issues in the independent curriculum of first grade elementary schools on Pancasila Education Learning, which has been validated. This research is included in the category of research development or Research and Development. This study uses the Borg and Gall (1979) model which consists of 10 development processes. However, researchers only carry out development up to step seven, this is because up to step seven can already answer the formulation of the problem in this study and researchers can only produce media on a small scale within limited time. Interviews are data collection instruments used in the exploration stage, while the Likert scale and learning media assessment sheets are used in the product feasibility assessment stage to test the validity of the flashcard media. The results showed that the Flash Cards learning media was in a position that was very feasible to use with an average acquisition of validation results by 2 validators of 77.5% and an assessment result by class teachers of 80.6%.